Severe consequences of uncontrolled tertiary hyperparathyroidism in a limited resources setting: a case report - Mejía Raudales, Beatriz; Portillo Muñoz, Carlos Andres; Chavez, Genesis Sarahi; Gough, Simmons (Frontiers in Nephrology, 2025)
Tertiary hyperparathyroidism (THPT) is a severe complication of uncontrolled secondary hyperparathyroidism, typically associated with advanced-stage chronic kidney disease (CKD). We present the case of a Honduran patient with a long-standing history of CKD secondary to severe preeclampsia, who developed THPT following the discontinuation of her treatment due to financial constraints and the COVID-19 pandemic. The patient exhibited severe maxillofacial deformities, functional limitations, and widespread skeletal abnormalities. Despite initial management with medications such as paricalcitol and alfacalcidol, the lack of access to appropriate therapies and the postponement of a planned parathyroidectomy worsened her condition. This case highlights the importance of early diagnosis and timely intervention, particularly in resource-limited settings, emphasizing the urgent need for kidney transplant programs and improved preventive strategies in developing countries.